Betulinic Acid Alleviates Spleen Oxidative Damage Induced by Acute Intraperitoneal Exposure to T-2 Toxin by Activating Nrf2 and Inhibiting MAPK Signaling Pathways - Li Kong; Lijuan Zhu; Xianglian Yi; You Huang; Haoqiang Zhao; Yazhi Chen; Zhihang Yuan; Lixin Wen; Jing Wu; Jine Yi (Antioxidants, 2021)
T-2 toxin, which is mainly produced by specific strains of Fusarium in nature, can induce immunotoxicity and oxidative stress, resulting in immune organ dysfunction and apoptosis. Betulinic acid (BA), a pentacyclic triterpenoids from nature plants, has been demonstrated to possess immunomodulating and antioxidative bioactivities. The purpose of the study was to explore the effect of BA on T-2 toxin-challenged spleen oxidative damage and further elucidate the underlying mechanism. We found that BA not only ameliorated the contents of serum total cholesterol (TC) and triglyceride (TG) but also restored the number of lymphocytes in T-2 toxin-induced mice. BA dose-dependently reduced the accumulation of reactive oxygen species (ROS), enhanced superoxide dismutase (SOD) activity, and decreased malondialdehyde (MDA) content, as well as increased the total antioxidant capacity (T-AOC) in the spleen of T-2-toxin-exposed mice. Moreover, BA reduced inflammatory cell infiltration in the spleen, improved the morphology of mitochondria and enriched the number of organelles in splenocytes, and dramatically attenuated T-2 toxin-triggered splenocyte apoptosis. Furthermore, administration of BA alleviated the protein phosphorylation of p38, c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinases (ERK); decreased the protein expression of kelch-like erythroid cell-derived protein with CNC homology [ECH]-associated protein1 (Keap1); and increased the protein expression of nuclear factor erythroid 2 [NF-E2]-related factor (Nrf2) and heme oxygenase-1 (HO-1) in the spleen. These findings demonstrate that BA defends against spleen oxidative damage associated with T-2 toxin injection by decreasing ROS accumulation and activating the Nrf2 signaling pathway, as well as inhibiting the mitogen-activated protein kinase (MAPK) signaling pathway.